Copper strip tin plating process
By plating the nickel barrier layer, the first tin layer, the nickel intermediate layer and the second tin layer on the copper strip, the problem of insufficient dendrites on the tin surface is solved, and a stronger and more stable plating is achieved. Suitable for high temperature and high humidity environments.
Patent Information
- Application Number
- CN202411701503.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-14
AI Technical Summary
The prior art is difficult to effectively suppress the growth of dendrites on the surface of tin in copper-tin coating, affecting the strength and mechanical and electrical properties of the coating, and insufficient adhesion under high temperature and high humidity conditions.
Using a copper tape tin plating process, including plating a nickel barrier layer, a first tin layer, a nickel intermediate layer and a second tin layer on the copper tape substrate, through the interaction of the nickel layer and the tin layer and the collaboration of a specific structure, Improve the adhesion of the surface dendrites and cladding of the Sn plating.
It effectively inhibits the growth of dendrites on the surface of Sn plating, improves the adhesion and stability of the plating, and is suitable for use in high temperature and high humidity environments.
Smart Images

Figure CN119433649A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a metal plating process and products produced by the metal plating process, and in particular to a copper strip (nickel) tin plating process and a corresponding copper strip (nickel) tin plating process. Background Art
[0002] With the rapid development of industrial upgrading and various industries, existing material products need to be continuously improved according to industrial upgrading. For example, copper strip plating products are not only used in semiconductor and precision device industries and fields, but also in new industries such as wind power and photovoltaics, which pose new challenges to the application of materials. Under high temperature, high humidity and even certain pressure conditions, higher requirements are placed on the durability and adhesion of the Sn coating on the Cu base strip.
[0003] In the testing and research of copper-tin plating, it is generally believed that the growth of whiskers on the Sn surface will destroy the surface state of the copper-tin material, thereby affecting the strength and mechanical and electrical properties of the coating. There are currently many analyses of factors that may affect the growth of whiskers on the tin surface (such as plating solution composition and semiconductor packaging). The spontaneous whisker growth phenomenon during high temperature and high humidity is usually attributed to the compressive stress or stress gradient accumulated in the tin plating during the formation of Cu6Sn5 type intermediate metal compounds (IMC). Studies have shown that adding an appropriate amount of Pb to the Sn plating solution can inhibit the growth of whiskers, but as industry rules and laws have increasingly stringent requirements for environmental protection, adding environmentally harmful components such as Pb to a large number of products is becoming increasingly undesirable.
[0004] There are also studies on improving the quality of Sn coatings through other plating solutions and coating components. For example, U.S. Patent US2008 / 0050611A involves adding other precious metal components to the tin plating solution, which contains elements such as cobalt and silver. However, the use of precious metals and cobalt has affected the industrial-scale promotion and application, and has not solved the strength and performance problems of Sn coatings in a better way. There are also studies using continuous multi-layer tin plating processes to try to reduce the problem of dendrite growth on the Sn surface. However, the inventors found through comparative studies that the continuous tin plating process cannot completely and permanently solve the problem of Sn dendrite growth, and multi-layer tin plating also has a negative impact on the adhesion of the surface Sn coating. Summary of the invention
[0005] The present invention aims to solve one or more of the above-mentioned deficiencies in the prior art, and utilizes the interaction between the tin layer and the nickel layer and the cooperation of the specific structure to improve the adhesion problem of the surface dendrites and the coating of the Sn coating.
[0006] A first aspect of the present invention provides a copper strip tinning process, the copper strip tinning process comprising the following steps:
[0007] Step 1) preparing a copper tape substrate;
[0008] Step 2) plating a nickel barrier layer on the copper strip substrate;
[0009] Step 3) plating a first tin layer on the nickel barrier layer;
[0010] Step 4) plating a nickel intermediate layer on the first tin layer;
[0011] Step 5) plating a second tin layer on the nickel intermediate layer; and
[0012] wherein the lower surface of the nickel intermediate layer directly contacts the upper surface of the first tin layer, and the upper surface of the nickel intermediate layer directly contacts the lower surface of the second tin layer; and
[0013] In the tinned copper strip prepared by the copper strip tinning process, the thickness of the nickel barrier layer is approximately 1.5 to 5 microns, the thickness of the nickel intermediate layer is approximately 1 to 3 microns, the thickness of the nickel intermediate layer is less than or equal to the thickness of the nickel barrier layer, and the thickness of the second tin layer is approximately 1 to 3 microns.
[0014] In an optional technical solution, in the nickel barrier layer plating process of step 2), a continuous electroplating process is adopted, wherein the plating solution of the nickel barrier layer includes Ni(NH2SO3)2.4H2O, whose content is 400 to 800 g / L; NiCl2.6H2O, whose content is 20 to 50 g / L; boric acid solution, whose content is 30-80 g / L; the plating solution of the nickel barrier layer further optionally includes an auxiliary component, the auxiliary component is selected from isopropyl glycol and / or naphthol polyoxyethylene ether, and the content of isopropyl glycol and / or naphthol polyoxyethylene ether is 1-20 g / L respectively, and
[0015] The plating temperature of the nickel barrier layer plating process is set to 40-60°C, and the current density is set to 3-6A / dm 2 ;as well as
[0016] The nickel barrier layer plating process is configured such that the thickness of the nickel barrier layer is greater than or equal to the thickness of the nickel intermediate layer.
[0017] In an optional technical solution, in the plating of the first tin layer in step 3), a continuous electroplating process is adopted, and the first tin layer plating solution includes stannous methanesulfonate, with a content of 100-200 g / L; methanesulfonic acid, with a content of 10-50 g / L; ethylenediaminetetraacetic acid, with a content of 10-40 g / L; the first tin layer plating solution also includes auxiliary components, and the auxiliary components are selected from alkylphenol polyoxyethylene ether and / or hydroxyethylene diphosphonic acid, and the content of the alkylphenol polyoxyethylene ether and / or hydroxyethylene diphosphonic acid is 1 to 15 g / L respectively; and
[0018] The thickness of the first tin layer is 0.5 to 2 micrometers; and
[0019] After electroplating the first tin layer, the copper strip plated with the nickel barrier layer and the first tin layer is placed in an annealing furnace for annealing at a temperature of 100 to 130° C. for 1 to 3 hours.
[0020] In an optional technical solution, in the process of plating the nickel intermediate layer in step 4), the nickel intermediate layer plating solution includes Ni(NH2SO3)2.4H2O, whose content is 500 to 800 g / L; NiCl2.6H2O, whose content is 30 to 60 g / L; boric acid, whose content is 60 to 90 g / L; the nickel intermediate layer plating solution further optionally includes an auxiliary component selected from isopropyl glycol and / or isopropyl glycol, and the content of the isopropyl glycol and / or isopropyl glycol is 1-20 g / L respectively;
[0021] The electroplating process temperature of the nickel intermediate layer is 40 to 50° C. and the current density is 3 to 6 A / dm 2 ; and wherein the electroplating time of the nickel plated intermediate layer is less than the electroplating time of the nickel barrier layer process, so that the thickness of the nickel intermediate layer is less than or equal to the thickness of the nickel barrier layer; and
[0022] At least a portion of the nickel-clad intermediate layer generates Ni-containing dendrites growing in a direction perpendicular to the outer surface of the tin-plated copper strip.
[0023] In an optional technical solution, in the process of plating the second tin layer in step 5), the second tin layer plating solution includes stannous methanesulfonate, whose content is 100-150 / L; methanesulfonic acid, whose content is 10-50g / L; ethylenediaminetetraacetic acid, whose content is 10-50g / L; the second tin layer plating solution also includes auxiliary components selected from alkylphenol polyoxyethylene ether and / or hydroxyethylene diphosphonic acid, and the content of the alkylphenol polyoxyethylene ether and / or hydroxyethylene diphosphonic acid is 1 to 10g / L respectively; and
[0024] The current density of the process of the second tin layer is less than the current density of electroplating the first tin layer, and the electroplating time of the process of the second tin layer is greater than or equal to the electroplating time of plating the first tin layer, so that the thickness of the second tin layer is 1 to 3 microns.
[0025] In an optional technical solution, the copper strip tinning process specifically includes the following steps:
[0026] Step 1) preparing a copper tape substrate: cleaning the copper tape to remove oxides on its surface;
[0027] Step 2) Plating a nickel barrier layer on the copper strip substrate: placing the cleaned copper strip in a plating solution of a nickel barrier layer plating process, wherein the plating solution of the nickel barrier layer plating process includes 550 g / L Ni(NH2SO3)2.4H2O, 50 g / L NiCl2.6H2O, 65 g / L boric acid solution, 10 g / L isopropyl glycol, and 10 g / L naphthol polyoxyethylene ether; the pH value of the plating solution is controlled at about 2 to 3, the electroplating temperature is 40°C-45°C, and the current density is 5A / dm 2 , using a continuous electroplating process; the plating thickness of the nickel barrier layer is 2.5 to 3 microns;
[0028] Step 3) plating a first tin layer on the nickel barrier layer: placing the copper strip plated with the nickel barrier layer in step 2) into a first tin layer plating solution, wherein the first tin layer plating solution comprises 150 g / L of stannous methanesulfonate, 30 g / L of methanesulfonic acid, and 25 g / L of ethylenediaminetetraacetic acid, and the first tin layer plating solution also comprises auxiliary components, 15 g / L of alkylphenol polyoxyethylene ether and 5 g / L of hydroxyethylene diphosphonic acid; and
[0029] The electroplating temperature of the first tin layer is 30 to 35°C and the current density is 2A / dm 2 , using a continuous electroplating process, the thickness of the first tin layer is 1 to 1.5 microns; and
[0030] After electroplating the first tin layer, placing the copper strip plated with the nickel barrier layer and the first tin layer into an annealing furnace for annealing at a temperature of 120° C. for a holding time of 2 hours;
[0031] Step 4) Plating a nickel intermediate layer on the first tin layer: placing the copper strip sample after the first tin layer is plated and annealed into a plating solution for preparing an intermediate nickel layer, wherein
[0032] The nickel intermediate layer plating solution includes 650 g / L Ni(NH2SO3)2.4H2O, 60 g / L NiCl2.6H2O, 80 g / L boric acid, 10-20 g / L isopropyl glycol and 10-20 g / L naphthol polyoxyethylene ether;
[0033] The pH value of the nickel intermediate layer plating solution is controlled to be about 2, the electroplating temperature is 40 to 45°C, and the current density is 6A / dm 2 , wherein the electroplating time of the nickel intermediate layer is less than the electroplating time of the nickel barrier layer process, and the thickness of the nickel intermediate layer is 1.5 to 2 microns, thereby obtaining a copper strip with a nickel intermediate layer;
[0034] Step 5) Plating a second tin layer on the nickel intermediate layer: placing the copper strip with the nickel intermediate layer into a second tin layer plating solution,
[0035] The second tin layer plating solution comprises 120 g / L of stannous methanesulfonate, 20 g / L of methanesulfonic acid, 20 g / L of ethylenediaminetetraacetic acid, 10 g / L of alkylphenol polyoxyethylene ether and 1-5 g / L of hydroxyethylenediphosphonic acid; and
[0036] The current density of the second tin layer process is controlled to be 1.5A / dm 2 The electroplating temperature is 30 to 35° C., and the electroplating time of the second tin layer process is greater than the electroplating time of plating the first tin layer, so that the thickness of the second tin layer is 1.5 to 2.5 microns.
[0037] Another aspect of the present invention provides a tinned copper strip, wherein the tinned copper strip comprises a copper strip base and a tin coating layer located on the uppermost layer, and the tinned copper strip has a nickel layer and a tin layer plated alternately stacked on each other, and comprises:
[0038] a nickel barrier layer disposed on the copper strip substrate;
[0039] a first tin layer plated on the nickel barrier layer;
[0040] at least one nickel intermediate layer, wherein the lower surface of the nickel intermediate layer directly contacts the upper surface of the first tin layer;
[0041] a second tin layer disposed on the nickel intermediate layer, wherein a lower surface of the second tin layer directly contacts an upper surface of the nickel intermediate layer; and
[0042] The thickness of the nickel barrier layer is about 1.5 to 5 microns, the thickness of the nickel intermediate layer is about 1 to 3 microns, the thickness of the nickel intermediate layer is less than or equal to the thickness of the nickel barrier layer, and the thickness of the second tin layer is about 1 to 3 microns.
[0043] In an optional technical solution, the tinned copper strip has at least one of the following structures:
[0044] The thickness of the nickel barrier layer is greater than the thickness of the nickel intermediate layer;
[0045] At least a portion of the upper surface of the first tin layer generates tin-containing dendrites growing along the upper surface of the tin layer;
[0046] At least a portion of the upper surface of the nickel intermediate layer is convex, and the second tin layer evenly covers the convexity of at least a portion of the upper surface of the nickel intermediate layer; and / or
[0047] At least a portion of the nickel-clad intermediate layer generates Ni-containing dendrites that grow in a direction perpendicular to the outer surface of the tin-plated copper strip, and a protrusion is generated on the upper surface of the Ni-containing dendrite.
[0048] The tinned copper strip of the present invention can be prepared by using the copper strip tinning process described in any one of the above methods.
[0049] The tinned copper strip and the copper strip tinning process provided by the present invention effectively improve the problem of the generation and spread of surface tin dendrites that are insufficient in the related art, and also effectively improve and maintain the adhesion of the tin surface layer. This will be further explained in the following specific embodiments.
[0050] In the following, the technical solutions and advantages of the present invention will be explained and described in more detail in conjunction with specific implementation methods. It should be understood that the contents presented in the specification and specific implementation methods are only for the purpose of more clearly illustrating the technical solutions and advantages of the present invention, and do not limit the protection scope of the present invention. Those skilled in the art can obtain the changed technical solutions based on the disclosure of the specification for various reasonable transformations. As long as they do not deviate from the spirit of the present invention, the various changed technical solutions should be understood to be included in the protection scope of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] The accompanying drawings are used to provide a further understanding of the technical solution of the present disclosure and constitute a part of the specification. Together with the specific embodiments of the present application, they are used to explain the technical solution of the present disclosure and do not constitute a limitation on the technical solution of the present disclosure.
[0052] Figure 1 1 is a SEM electron microscope photo of the upper surface of the tinned copper strip manufactured according to Example 1 of the present invention and Comparative Example 1. Figure 1 (a) is a SEM electron microscope photograph of the upper surface of the tinned copper strip manufactured according to Example 1, Figure 1 (b) is a SEM electron microscope photograph of the upper surface of the tinned copper strip manufactured according to Comparative Example 1;
[0053] Figure 2 is a cross-sectional SEM electron microscope photograph of a tinned copper strip manufactured according to Example 1 and a schematic diagram of a key coating layer;
[0054] Figure 3 It is a cross-sectional SEM electron microscope photograph of the tinned copper strip manufactured according to Comparative Example 1 and a schematic diagram of the key coating layer. DETAILED DESCRIPTION
[0055] The present invention is described in more detail hereinafter to facilitate understanding of the invention.
[0056] Before describing the specific implementation scheme, it should be noted that those skilled in the art can select appropriate raw materials according to the enlightenment and teaching of the present disclosure, and use relevant testing equipment to perform relevant tests and obtain corresponding results. For raw materials without specific manufacturers or pathways, those skilled in the art can select raw materials that meet corresponding requirements as reaction starting materials according to the disclosure and requirements of this specification. The reaction raw materials of the process part compounds are derived from the initial products synthesized in the preamble step of the present invention, which can also be understood according to the present disclosure.
[0057] First, the main raw materials used in the present invention and the corresponding acquisition channels or raw material origins are listed in Table 1. It should be noted that the raw materials not described in the present invention are raw material varieties that can be obtained by those skilled in the art based on common technical knowledge and existing market products.
[0058] Table 1: Description of the main raw materials used in the present invention
[0059]
[0060] It should be noted that percentages indicated in the technical solution, embodiments of the specification and the summary of the invention are generally specifically described. If no special description is made on the concentration or percentage, it refers to the mass percentage (wt%) or a unit related to mass, such as gram / liter (g / L). For example, the phosphoric acid solution used in the embodiment can be a phosphoric acid solution with a mass concentration of 1-5%, and a typical mass concentration can be 3%.
[0061] In addition, the present invention may adopt an open-ended component definition method such as "includes" or "comprising" to indicate that the embodiment of the present invention may include the main component / coating used, and may also include other subsidiary components / coatings. However, in a preferred embodiment of the present invention, it may only consist of the various components and coatings defined in the present invention, without having to include any other components. For example, two nickel layers (bottom nickel barrier layer and middle nickel layer) and two tin layers (first tin coating layer and top tin coating layer) are described in the embodiment of the present invention; however, the design concept of the present invention is not limited to this, and the technical solution of the present invention may include other layers, such as three nickel layers and three tin layers arranged alternately with each other, or four nickel layers and four tin layers arranged alternately; at the same time, in a preferred embodiment, the tin-plated copper strip of the present invention may only consist of the first nickel layer (nickel barrier layer), the first tin layer, the middle nickel layer and the second tin layer (top tin layer) adjacent to each other and stacked in sequence, without having or including other intermediate layers or other coatings with significant main components.
[0062] The schematic diagram of the present invention is intended to clearly describe the structural and morphological characteristics of the key parts of the coating layer (such as dendrites, protrusions, etc.), and does not necessarily represent the size and relationship of each grain in each layer in proportion. This can be verified from the process of the present invention and the SEM electron microscope photographs.
[0063] Test experiment of the present invention
[0064] Before beginning to describe the preparation experimental examples, the test process, standards, and characterization methods used in typical experiments of the present invention are briefly described.
[0065] 1. Wet heat test and hot and cold cycle test of tinned copper strip
[0066] In a typical test experiment, the test process of this experiment is roughly described as follows:
[0067] The whisker suppression effect of the tinned copper strip obtained by the copper strip tinning process of the present invention was simulated by using a damp heat test and a hot and cold cycle test in a typical environment. Before the test, the copper strips prepared in the embodiment or the comparative experiment were respectively made into lead frames by processes such as stamping and bending, and then kept warm at 90°C for 0.5 hours as a preheating process, and then the samples were subjected to a damp heat test and a hot and cold cycle test.
[0068] Wet heat test of tinned copper strip samples: stored at 90℃ and 90%RH for 2500 hours. Stored at 50℃ / 85%RH for 5000 hours.
[0069] Hot and cold cycle test of tinned copper strip samples: 2000 cycles were completed at -60℃ to 130℃, with high and low temperatures lasting 15 minutes respectively.
[0070] 2. Tin coating adhesion test
[0071] The copper strip samples of the examples or comparative experiments were kept in a conventional convection oven at 180°C for 1000 hours. The adhesion of the tin layer on the samples was measured every 100 hours, wherein the samples were cooled to room temperature and the adhesion of the Sn layer on each sample was tested by a standard orthogonal test and a tape test. The test was terminated after 1000 hours.
[0072] In the tape adhesion test results, if there is no visible coating material (Sn) in the adhesive tape, the score is 1 (excellent); if point-like scattered coating material is found in the tape, the score is 2 (qualified); if linear continuous adhesion coating material is found in the tape, the evaluation is 3 points (unqualified).
[0073] Incidentally, the sample electron microscope test of the present invention typically uses a Schottky Field Emission Scanning Electron Microscope of model FEISirion200. However, the test conditions are not limited to a specific electron microscope device. As long as the metallographic sample preparation conditions and sample test conditions are met, other similar types of electron microscope devices can also be used.
[0074] According to the following described embodiments and comparative experiments of the present invention, a manufacturing process for inhibiting the diffusion and growth of whiskers in single-layer or multi-layer tin-plated copper strip products will be provided and prepared, and the adhesion between the plating layers can also be enhanced. The copper strip can be used stably for a long time in a high temperature and high humidity environment, and is suitable for the use needs of copper strip substrates in harsh environments, such as outdoor photovoltaics, power generation, and high-temperature semiconductor process fields.
[0075] Example 1
[0076] This embodiment describes the manufacturing process and procedure of a typical multi-layer composite tinned copper strip.
[0077] The cleaned copper strip sample 20cm × 2cm copper-based samples (prepare 2 to 3 identical copper strips), the oxides that may exist on the surface of the copper strips can be removed using known techniques. Afterwards, the samples are placed in the nickel electroplating solution described in Table 1. Optionally, the surface of the Cu strip can be properly polished with sandpaper, thereby forming micro-roughness that is beneficial to the plating of the coating.
[0078] Table 1: First nickel barrier layer plating solution formula and experimental conditions (aminosulfonic acid nickel plating solution)
[0079]
[0080] During the nickel plating process, the sample was connected to a rectifier and a continuous nickel plating process was used. During the nickel plating process, the current intensity, temperature, concentration of the reaction solution, etc. remained basically stable. The counter electrode was a platinum-plated titanium electrode. During the nickel plating process, the temperature of the nickel plating solution was maintained at 40-45 degrees Celsius. The current density was 5A / dm 2 The electroplating was stopped when a nickel layer with a thickness of 2.5 to 3 μm was deposited on the surface of the copper sample. The sample was taken out of the plating solution and rinsed with deionized water at room temperature to obtain a Cu tape substrate with a nickel-plated barrier layer.
[0081] In the present invention, the inventor hopes to set the bottom nickel barrier layer to be thicker, so as to facilitate the subsequent setting of the Sn and Ni composite layer.
[0082] Next, the nickel-plated barrier layer substrate is placed in a matte tin plating solution. In this embodiment, the matte tin plating solution may be composed of the following components:
[0083] Table 2: First tin layer plating solution formula and experimental conditions (matte tin or matte tin plating solution)
[0084]
[0085]
[0086] The first tin layer plating solution and the electroplating process ensure that the first tin layer (bottom Sn layer) is electroplated on the above-mentioned nickel-plated barrier layer substrate with a thickness of 1 to 1.5 μm to obtain a bottom Sn layer copper strip substrate.
[0087] Next, the bottom Sn layer copper strip substrate is typically placed in an annealing device and annealed at 120°C for 2 hours. After the product is cooled, it is placed again in the plating solution for preparing the intermediate nickel layer:
[0088] Table 3: Intermediate nickel layer plating solution formula and experimental conditions (aminosulfonic acid nickel plating solution)
[0089]
[0090] In the intermediate nickel layer plating solution, the concentration of nickel sulfamate and / or nickel chloride used is greater than the concentration of the corresponding raw materials in the first nickel barrier layer plating solution, and the electroplating time is shorter than the first nickel barrier layer plating process, so that the thickness of the intermediate Ni layer is less than or equal to the first nickel layer (nickel barrier layer). In this embodiment, the thickness of the intermediate Ni layer is controlled to be 1.5 to 3 μm (preferably, controlled to be 2-2.5 μm). A copper strip plated with an intermediate nickel layer is obtained.
[0091] Next, the copper strip plated with the intermediate nickel layer is placed in the second tin layer plating solution (surface tin layer) to perform the second tin layer plating process:
[0092] Table 4: Second tin layer plating solution formula and experimental conditions (matt tin plating solution)
[0093]
[0094] In the second tin layer plating process, the process settings make the tin layer grow more moderate, wherein the concentrations of stannous methanesulfonate and methanesulfonic acid are lower than the raw material concentrations in the first tin layer plating process, the second tin plating current density used is less than the first tin plating current density, and the second tin plating time is greater than or equal to the time of the first tin plating process, to obtain a second tin plating layer (top tin layer) with a thickness of 1.5 to 2.5 microns.
[0095] After the manufacturing example is completed, the tinned copper strip samples are subjected to the wet heat test and the hot and cold cycle test under the conditions of the aforementioned part. The copper strip samples after the wet heat test and the hot and cold cycle test are tested by field emission scanning electron microscope (FESEM). The results are shown in Figure 1 .
[0096] exist Figure 1 The left FESEM image ( Figure 1 (a) shows the structure of the surface of the tin-plated layer of the copper strip prepared according to Example 1 of the present invention. Figure 1 It can be seen from the view on the left that after the harsh wet heat test and hot and cold cycle test, the tin surface presents almost a dot-like flat distribution on the surface. Even if there are very small amounts of micro-protrusions or micro-depressions, it hardly affects the flatness of the surface of the tin plating layer, and there is almost no striped dendrite growth on the surface, indicating that the process of this embodiment and the obtained product have effectively suppressed the state and problem of dendrite growth of the Sn plating material.
[0097] Next, the Sn coating adhesion test was performed on the sample of Example 1. In the single orthogonal tape test on the sample of Example 1, the Sn coating showed good adhesion, and the results were excellent within the 1000-hour test period.
[0098] The inventor will attempt to make non-limiting explanations and illustrations of the present invention concept and corresponding effects in the following further tests and comparative experiments.
[0099] Comparative Example 1
[0100] Relevant studies and reports suggest that after a nickel barrier layer is plated on the bottom of a metal substrate, one or more Sn layers are continuously plated on the Ni barrier layer, wherein the Sn layers are in direct contact and stacked with each other, which can improve the crystal growth problem of the Sn coating. In view of this, the inventors designed the following series of comparative experiments to conduct comparative studies with the technical solutions of the embodiments.
[0101] In Comparative Example 1, a 20 cm copper strip sample was prepared as in Example 1. × A 2 cm copper-based sample was subjected to the same first nickel barrier layer plating process. After the first nickel barrier layer plating process was completed, the first tin layer plating process was performed in the same manner as in Example 1 to obtain a composite metal stack of a copper substrate, a first nickel barrier layer and a first Sn-plated layer.
[0102] Different from Example 1, after the above steps, no annealing process is performed, and the intermediate Ni layer setting process of Example 1 is not adopted, but a second tin layer plating process is directly adopted, that is, a second Sn layer is directly plated on the first plated Sn layer. For the convenience of comparison, the second tin layer plating process in Comparative Example 1 adopts the same electroplating parameters as the second tin layer plating process in Example 1.
[0103] The tinned copper strip products completed according to the above process are also subjected to the wet heat test and hot and cold cycle test under the above conditions. After the samples have undergone the wet heat test and hot and cold cycle test, the copper strip samples are tested by field emission scanning electron microscope (FESEM). The results are also shown in Figure 1 The right picture ( Figure 1 (b)).
[0104] from Figure 1 As can be seen from (b), the right side of the Cu strip manufactured in Comparative Example 1 is basically flat, but from the middle of the sample to the left, a striped Sn surface gradually appears, extending in a dendrite state. At the same time, a striped depression appears in the middle of the sample, indicating that the adhesion of part of the coating may be deteriorated.
[0105] Next, the sample of comparative example 1 was subjected to a Sn coating adhesion test. In the single orthogonal tape test of the comparative sample, the Sn coating showed good adhesion (1 point, excellent) after the first 200 hours, and after 300 hours, scattered Sn distribution appeared on the tape (the tape Sn point distribution accounted for about 3%), and the evaluation was only passing (2 points). After 1000 hours, the tape showed some fine stripes of continuous coating material, and the coating adhesion result at 1000 hours was unqualified.
[0106] The inventors are not limited to any theory for the test results of the embodiments and comparative experiments. However, the inventors cut the samples of the tinned copper strips prepared in Example 1 and Comparative Example 1 longitudinally after the wet heat test and the hot and cold cycle test, polished the cross section according to the metallographic preparation process of Cu samples in the prior art, and then performed SEM tests on the cross section. The results are shown in Figure 2 and Figure 3 .
[0107] Figure 2 is a cross-sectional SEM electron microscope photograph of the tinned copper strip after the wet heat test and the hot and cold cycle test in Example 1 of the present invention, Figure 2 The following figure is a schematic depiction of the key layers. Figure 2 In the SEM electron microscope photo in the figure above, from bottom to top, the Cu strip substrate, the first Ni layer (i.e., the nickel barrier layer, the nickel barrier layer 10 in the schematic diagram below, the Cu substrate is omitted in the schematic diagram for convenience), the first Sn layer (the first Sn layer 20 in the figure below), the second nickel layer (i.e., the nickel intermediate layer, the nickel intermediate layer 40 in the figure below), and the second Sn layer (i.e., the top Sn layer) are shown in sequence. Figure 2The SEM in the upper part and the analytical schematic diagram of the key parts in the lower schematic diagram show that when the first Ni layer is plated on the Cu strip substrate, its growth is relatively flat; when the first Sn layer is directly plated on the first Ni layer, the surface of the Sn layer will produce obvious partial protrusions during the copper strip plating, annealing process and high temperature or high humidity use, and the annealing process of the first tin layer in the embodiment promotes the appearance of some dendrites, which appear as growing dendrites in the plane state of the tin-plated copper strip (such as Figure 2 Dendrite 30 shown in the figure below). The inventor surprisingly found that when a second nickel layer (i.e., nickel intermediate layer) is further plated on the Sn plated layer with dendrites, the protruding dendrites of the first Sn layer will induce the nickel plated layer to grow longitudinal columnar dendrites (such as Ni dendrite 40 in the figure below). When the second Sn layer (i.e., the top Sn layer) is plated and grown again in the next step, due to the relatively high hardness of Ni itself, it is the Ni dendrite 40 in the nickel intermediate layer that destroys the dendrite path that the top Sn layer may grow, resulting in the top Sn layer no longer producing dendrites that grow significantly along the plane. At the same time, after the top Sn layer flatly covers the nickel intermediate layer, the partial protrusions of the nickel intermediate layer can play a pinning role to enhance the adhesion of the top Sn layer.
[0108] Compared with Example 1, Figure 3 The cross-sectional SEM electron microscope photograph of the tinned copper strip after the wet heat test and the hot and cold cycle test in Comparative Example 1 is shown. Figure 3 The figure below is a schematic depiction of the key layers.
[0109] refer to Figure 3 In the test of the sample of comparative example 1, after plating the Ni barrier layer (Ni barrier layer 10 in the schematic diagram below) on the bottom Cu strip substrate, two layers of Sn layers were continuously plated. The inventors found that after the two layers of matte tin layers were continuously plated, the cracks or dendrites of the first Sn layer (the first Sn layer 20 in the schematic diagram below) were transferred to the second layer, causing part of the dendrites of the first Sn layer (the first Sn layer dendrites 130) to be transferred to the second Sn layer (the top Sn layer dendrites 140). At the same time, the continuous Sn plating cannot provide additional fixing force or pinning force for the top Sn plating layer. Figure 3 From the SEM image of the upper part, it can be seen that transverse stripe-like wrinkles appear in the top Sn layer, which corresponds to the dendrite growth phenomenon on the surface of the tin-plated copper strip.
[0110] Therefore, during the test, the test results of the tinned copper tape of Comparative Example 1, including the Sn dendrite growth in the wet heat test and the hot and cold cycle test and the tape adhesion test, were all deteriorated compared with the examples. Among them, significant dendrites were generated on the surface of Comparative Example 1 in the wet heat test and the hot and cold cycle test, and the adhesion evaluation for more than 200 hours in the wet heat test and the hot and cold cycle test was qualified or unqualified.
[0111] In an embodiment of the present invention, an intermediate Ni layer is formed on top of the first Sn layer, so that the dendrites existing on the surface of the first Sn layer are used to induce the growth of longitudinal dendrites (perpendicular to the direction of the copper strip surface) in the intermediate Ni layer, thereby inhibiting the growth of dendrites of the second Sn layer plated on the intermediate Ni layer. Due to the greater hardness of Ni itself, its small protruding longitudinal dendrites are conducive to "pinning" the surface Sn layer (such as the second Sn layer), thereby enhancing the adhesion of the plated layer.
[0112] In terms of the coating structure, the tin-plated copper strip in the embodiment of the present invention has one or more Ni intermediate layers, the lower surface of the Ni intermediate layer contacts a Sn coating (such as the first Sn coating on the nickel barrier layer), and the upper surface of the Ni intermediate layer contacts another Sn coating (such as the second Sn coating above the Ni intermediate layer, or the second Sn coating is used as the top Sn coating of the copper strip). The second Sn coating is plated on the upper surface of the Ni intermediate layer in a flat surface state.
[0113] The inventors found through comparative experiments and implementation plans that simply stacking multiple layers of tin plating layers cannot effectively and thoroughly solve the problem of surface dendrite propagation of the Sn surface layer under harsh conditions, and that multiple layers of Sn layers also have a negative impact on the firm adhesion of the surface Sn layer.
[0114] According to the performance requirements for the coating, such as toughness, adhesion, high temperature durability, etc., the embodiment of the present invention may include multiple Ni intermediate layers, such as two Ni intermediate layers or three Ni intermediate layers. Those skilled in the art can understand the arrangement and manufacturing method of multiple Ni intermediate layers and corresponding Sn coatings based on the contents disclosed in this specification.
[0115] Examples 2 to 5
[0116] In this embodiment series, the inventors appropriately adjusted the process parameters for plating Sn and Ni layers, and performed the same test method on the Cu strip product as in Embodiment 1. It should be noted that, for the convenience of description, the following table mainly describes the process parameters different from Embodiment 1, and the parameters not described can use the same process parameters as in the embodiment, or be set accordingly according to the process trend and purpose described in Embodiment 1.
[0117] Table 5: Partially adjusted plating process parameters in Examples 2 to 5
[0118]
[0119]
[0120] In the embodiment of the present invention, preferably, the content of Ni(NH2SO3)2.4H2O in the first nickel barrier layer plating solution is between 400 and 800 g / L, so that the thickness of the first nickel barrier layer is preferably between 1.5 and 5 μm, wherein under the same manufacturing process conditions, a thicker Ni barrier layer is conducive to inducing the growth of surface dendrites on the bottom Sn layer, thereby facilitating the growth of some longitudinal dendrites in the Ni intermediate layer that pins the top Sn layer. The content of Ni(NH2SO3)2.4H2O in the nickel intermediate layer can be between 500-800 g / L. It is worth noting that although the content of Ni raw material (such as nickel sulfamate) in the nickel intermediate layer can be greater than the Ni raw material in the Ni barrier layer, the plating current and time in the nickel intermediate layer plating process should be controlled so that the growth rate of the nickel intermediate layer is faster and the thickness is preferably thinner than or similar to the nickel barrier layer. This is because a faster electroplating speed is conducive to the formation of longitudinal dendrites in the subsequent nickel intermediate layer, while a too thick Ni intermediate layer is not conducive to the flatness of the top Sn layer.
[0121] Similarly, the content of stannous methanesulfonate in the second tin layer plating process can be between 100-150g / L, so that the thickness of the second tin plating layer (or the top Sn layer in multiple Sn plating layers) is greater than 1μm, and preferably less than 3μm. When the top Sn layer is too thin, it is possible to affect the flatness of the Sn layer surface, which may be affected by the slightly raised Ni longitudinal dendrites at its bottom. A too thick top Sn layer is not conducive to the pinning effect of the lower Ni layer and the suppression of surface dendrites. At the same time, a too thick Sn layer is not conducive to saving process costs.
[0122] Comparative Examples 2 to 5
[0123] Accordingly, the inventors also conducted some comparative experiments on process parameters, and the experimental results can be seen in the following table:
[0124] Table 5: Partially adjusted plating process parameters in Comparative Examples 2 to 5
[0125]
[0126]
[0127] From the results of the comparative experiment, when the amount of the bottom first nickel layer (Ni barrier layer) is too little, it may not be possible to induce the formation of an effective pinning structure of the middle Ni layer (such as comparative example 2). When the middle pinch layer grows too thick, it is also impossible to protect the flatness, adhesion and dendrite suppression of the top Sn layer. For the top Sn layer (such as the second Sn layer or more Sn layers), if the thickness is too small (such as less than 1 micron), it is impossible to ensure smooth plating on the middle Ni layer; and if the thickness is too large, it is not conducive to the suppression of dendrites and the protection of the adhesion of the coating surface.
[0128] According to the implementation scheme and technical contents recorded in the specification of the present invention, the present invention can at least provide the following technical solutions: Although the present disclosure includes specific embodiments, it is obvious to those skilled in the art that various formal and detailed replacements or changes can be made to these embodiments without departing from the gist and scope of the invention of the present claims and their equivalent technical solutions. The embodiments described herein should be considered to be illustrative only and not for the purpose of limitation. The description of the features and aspects in each embodiment is considered to be applicable to similar features and aspects in other embodiments. Therefore, the scope of the present disclosure should not be limited by the specific description, but by the technical solutions of the claims, and all changes within the scope of the claims and their equivalents are interpreted as being included in the technical solutions of the present disclosure.
Claims
1. A copper strip tinning process, characterized in that: The copper strip tinning process comprises the following steps: Step 1) preparing a copper tape substrate; Step 2) plating a nickel barrier layer on the copper strip substrate; Step 3) plating a first tin layer on the nickel barrier layer; Step 4) plating a nickel intermediate layer on the first tin layer; Step 5) plating a second tin layer on the nickel intermediate layer; and wherein the lower surface of the nickel intermediate layer directly contacts the upper surface of the first tin layer, and the upper surface of the nickel intermediate layer directly contacts the lower surface of the second tin layer; and In the tinned copper strip prepared by the copper strip tinning process, the thickness of the nickel barrier layer is approximately 1.5 to 5 microns, the thickness of the nickel intermediate layer is approximately 1 to 3 microns, the thickness of the nickel intermediate layer is less than or equal to the thickness of the nickel barrier layer, and the thickness of the second tin layer is approximately 1 to 3 microns.
2. The copper strip tinning process according to claim 1, characterized in that: In the nickel barrier layer plating process of step 2), a continuous electroplating process is adopted, wherein the plating solution of the nickel barrier layer includes Ni(NH2SO3)2.4H2O, whose content is 400 to 800 g / L; NiCl2.6H2O, whose content is 20 to 50 g / L; boric acid solution, whose content is 30-80 g / L; the plating solution of the nickel barrier layer further optionally includes auxiliary components, wherein the auxiliary components are selected from isopropyl glycol and / or naphthol polyoxyethylene ether, and the content of the isopropyl glycol and / or naphthol polyoxyethylene ether is 1-20 g / L respectively, and The plating temperature of the nickel barrier layer plating process is set to 40-60°C, and the current density is set to 3-6A / dm 2 ;as well as The nickel barrier layer plating process is configured such that the thickness of the nickel barrier layer is greater than or equal to the thickness of the nickel intermediate layer.
3. The copper strip tinning process according to claim 1, characterized in that: In the step 3), a continuous electroplating process is adopted in the plating of the first tin layer. The first tin layer plating solution includes stannous methanesulfonate in an amount of 100-200 g / L; methanesulfonic acid in an amount of 10-50 g / L; and ethylenediaminetetraacetic acid in an amount of 10-40 g / L. The first tin layer plating solution also includes an auxiliary component selected from alkylphenol polyoxyethylene ether and / or hydroxyethylene diphosphonic acid, and the content of each of the alkylphenol polyoxyethylene ether and / or hydroxyethylene diphosphonic acid is 1 to 15 g / L; and The thickness of the first tin layer is 0.5 to 2 micrometers; and After electroplating the first tin layer, the copper strip plated with the nickel barrier layer and the first tin layer is placed in an annealing furnace for annealing at a temperature of 100 to 130° C. for 1 to 3 hours.
4. The copper strip tinning process according to any one of claims 1 to 3, characterized in that: In the process of plating the nickel intermediate layer in step 4), the nickel intermediate layer plating solution includes Ni(NH2SO3)2.4H2O, whose content is 500 to 800 g / L; NiCl2.6H2O, whose content is 30 to 60 g / L; boric acid, whose content is 60 to 90 g / L; the nickel intermediate layer plating solution further optionally includes an auxiliary component selected from isopropyl glycol and / or isopropyl glycol, and the content of the isopropyl glycol and / or isopropyl glycol is 1-20 g / L respectively; The electroplating process temperature of the nickel intermediate layer is 40 to 50° C. and the current density is 3 to 6 A / dm 2 ; and wherein the electroplating time of the nickel plated intermediate layer is less than the electroplating time of the nickel barrier layer process, so that the thickness of the nickel intermediate layer is less than or equal to the thickness of the nickel barrier layer; and At least a portion of the nickel-clad intermediate layer generates Ni-containing dendrites growing in a direction perpendicular to the outer surface of the tin-plated copper strip.
5. The copper strip tinning process according to any one of claims 1 to 4, characterized in that: In the process of plating the second tin layer in step 5), the second tin layer plating solution includes stannous methanesulfonate, the content of which is 100-150 / L; methanesulfonic acid, the content of which is 10-50g / L; ethylenediaminetetraacetic acid, the content of which is 10-50g / L; the second tin layer plating solution also includes auxiliary components selected from alkylphenol polyoxyethylene ether and / or hydroxyethylene diphosphonic acid, and the content of each of the alkylphenol polyoxyethylene ether and / or hydroxyethylene diphosphonic acid is 1 to 10g / L; and The current density of the process of the second tin layer is less than the current density of electroplating the first tin layer, and the electroplating time of the process of the second tin layer is greater than or equal to the electroplating time of plating the first tin layer, so that the thickness of the second tin layer is 1 to 3 microns.
6. The copper strip tinning process according to any one of claims 1 to 5, characterized in that: The copper strip tinning process specifically comprises the following steps: Step 1) preparing a copper tape substrate: cleaning the copper tape to remove oxides on its surface; Step 2) Plating a nickel barrier layer on the copper strip substrate: placing the cleaned copper strip in a plating solution of a nickel barrier layer plating process, wherein the plating solution of the nickel barrier layer plating process includes 550 g / L Ni(NH2SO3)2.4H2O, 50 g / L NiCl2.6H2O, 65 g / L boric acid solution, 10 g / L isopropyl glycol, and 10 g / L naphthol polyoxyethylene ether; the pH value of the plating solution is controlled at about 2 to 3, the electroplating temperature is 40°C-45°C, and the current density is 5A / dm 2 , using a continuous electroplating process; the plating thickness of the nickel barrier layer is 2.5 to 3 microns; Step 3) plating a first tin layer on the nickel barrier layer: placing the copper strip plated with the nickel barrier layer in step 2) into a first tin layer plating solution, wherein the first tin layer plating solution comprises 150 g / L of stannous methanesulfonate, 30 g / L of methanesulfonic acid, and 25 g / L of ethylenediaminetetraacetic acid, and the first tin layer plating solution also comprises auxiliary components, 15 g / L of alkylphenol polyoxyethylene ether and 5 g / L of hydroxyethylene diphosphonic acid; and The electroplating temperature of the first tin layer is 30 to 35°C and the current density is 2A / dm 2 , using a continuous electroplating process, the thickness of the first tin layer is 1 to 1.5 microns; and After electroplating the first tin layer, placing the copper strip plated with the nickel barrier layer and the first tin layer into an annealing furnace for annealing at a temperature of 120° C. for a holding time of 2 hours; Step 4) Plating a nickel intermediate layer on the first tin layer: placing the copper strip sample after the first tin layer is plated and annealed into a plating solution for preparing an intermediate nickel layer, wherein The nickel intermediate layer plating solution includes 650 g / L Ni(NH2SO3)2.4H2O, 60 g / L NiCl2.6H2O, 80 g / L boric acid, 10-20 g / L isopropyl glycol and 10-20 g / L naphthol polyoxyethylene ether; The pH value of the nickel intermediate layer plating solution is controlled to be about 2, the electroplating temperature is 40 to 45°C, and the current density is 6A / dm 2 , wherein the electroplating time of the nickel intermediate layer is less than the electroplating time of the nickel barrier layer process, and the thickness of the nickel intermediate layer is 1.5 to 2 microns, thereby obtaining a copper strip with a nickel intermediate layer; Step 5) Plating a second tin layer on the nickel intermediate layer: placing the copper strip with the nickel intermediate layer into a second tin layer plating solution, The second tin layer plating solution comprises 120 g / L of stannous methanesulfonate, 20 g / L of methanesulfonic acid, 20 g / L of ethylenediaminetetraacetic acid, 10 g / L of alkylphenol polyoxyethylene ether and 1-5 g / L of hydroxyethylenediphosphonic acid; and The current density of the second tin layer process is controlled to be 1.5A / dm 2 The electroplating temperature is 30 to 35° C., and the electroplating time of the second tin layer process is greater than the electroplating time of plating the first tin layer, so that the thickness of the second tin layer is 1.5 to 2.5 microns.
7. A tinned copper strip, wherein the tinned copper strip comprises a copper strip base and a tin coating located on the uppermost layer, characterized in that: The tinned copper strip has nickel layers and tin layers that are alternately stacked and plated on each other, and comprises: a nickel barrier layer disposed on the copper strip substrate; a first tin layer plated on the nickel barrier layer; at least one nickel intermediate layer, wherein the lower surface of the nickel intermediate layer directly contacts the upper surface of the first tin layer; A second tin layer is disposed on the nickel intermediate layer, wherein a lower surface of the second tin layer directly contacts an upper surface of the nickel intermediate layer; and The thickness of the nickel barrier layer is about 1.5 to 5 microns, the thickness of the nickel intermediate layer is about 1 to 3 microns, the thickness of the nickel intermediate layer is less than or equal to the thickness of the nickel barrier layer, and the thickness of the second tin layer is about 1 to 3 microns.
8. The tinned copper strip according to claim 7, characterized in that: The tinned copper strip has at least one of the following structures: The thickness of the nickel barrier layer is greater than the thickness of the nickel intermediate layer; At least a portion of the upper surface of the first tin layer produces tin-containing dendrites growing along the upper surface of the tin layer; At least a portion of the upper surface of the nickel intermediate layer is convex, and the second tin layer evenly covers the convexity of at least a portion of the upper surface of the nickel intermediate layer; and / or At least a portion of the nickel intermediate layer generates Ni-containing dendrites that grow in a direction perpendicular to the outer surface of the tin-plated copper strip, and a protrusion is generated on the upper surface of the Ni-containing dendrite.
9. The tinned copper strip according to claim 7 or 8, characterized in that: The tinned copper strip is prepared by the copper strip tinning process according to any one of claims 1 to 6.
Citation Information
Patent Citations
Tin-Based Plating Film and Method for Forming the Same
US20080050611A1
Cited By
Method for designing thickness of Ni barrier layer in welding spot
CN120197582A
A Design Method for the Thickness of Ni Barrier Layer in Solder Joints
CN120197582B